DAMPAK EKONOMI PENAMBANG PASIR DI KAMPUNG KEPALA BANDAR NAGARI KUDO-KUDO INDERAPURA KABUPATEN PESISIR SELATAN - Irfantony, Riky - (Pendidikan Sosiologi, 2014)
Socio-economic problems is a problem that still haunts people in indonesia who never ending, some socio-economic problems it is still a low level of education, lack of employment opportunities open to the public and low income levels ,it is exactly what encourages people to explore and exploid the resource nature for the neccessities of life and the need to improve the socio-economic one natural resource that can be utilized one stand mining. This thesis describes how the sand miners in the social and economic life in the village head bookie, which works to alleviate the economic needs of the family.This study aims to look at the impact and social and economic life of the sand miners in the village chief seaport village kudo-kudo Inderapura shouthem coastal coanties .This research analyzed using type theory solidarity Emile Durkheim.This study used a qualitative approach with the method of observation and interviews.this research using primary and secondary sources, the primary source of information and researchers can related to sand miners Head Airport which can be combinet with interviews.For secondary sources the authors used data from the documentation of village councils with regard to writing this esay .Based on the result of this study concluded that the economic impact on the villageÂ chief seaport village kudo-kudo inderapura is the positive impact of opening new jobs ,menggiat small industries, changes in the pattern of livelihood.The negative impacts of conflict between the miners and the communities arround the mine,the destructions of social infrastructures (roads).